The data of alcohol. (Journal of Parents and Teachers, 2014)
Knowing that alcohol is currently abused concerns the whole society. Therefore, it is necessary to reflect on the drink from the figures offered in the article. In addition, it is exposed that alcohol is the most important drug in our society and the most consumed one.
Keywords: Alcohol; figures; percentages; alcohol abuse; drugs.